CONSTITUTIONAL LAW QUO VADIS: THE CONSTITUTION AND THE STATE OF LAW OF INDONESIA - Ruslan Ruslan; Haerani Husaniy (Omnibus Law Journal, 2022)
Constitutions are basically the work of human beings which is arranged according to the needs when they are made. The term constitution with the constitution is indeed in accordance with the Dutch and German habits of using the words Grondwet (Grond: basic, wet: law), and Grundgesetz (Grund: basic, Gesetz: law), both of which refer to written texts. The Constitution is “a text that describes the framework and main tasks of the government agencies of a country and determines the main points of how these bodies work. The constitution is made by the people to form a government, not the other way around it is set by the government for the people, the constitution precedes the government because the government is actually formed based on the constitution. The constitution existed before the government”. As a written constitution, the 1945 Constitution is the highest provision in the hierarchy of laws and regulations in Indonesia. The purpose of this paper is to find out how the concept of the ideal state of law is in accordance with the ideals of the Indonesian nation. The writing approach method is normative juridical. The conclusion of this research is that the State of Indonesia is a Pancasila state law, not a legal state in the western concept. Keywords : Constitution, State of Law, Pancasila.